АНТРОПОТОПОНИМЛАР: НОМЛАШ ҚОНУНИЯТЛАРИ ВА ҲУДУДИЙ ТАФОВУТЛАРИ ҲАҚИДА - Хакимов, К.М.; Сейтниязов, К.М. (SCIENCE and SOCIETY, 2021)
This article is viewed some laws of names and territorical variety of antropotoponims, as well as their scientific, politic and practical significance. Also with concrete examples are researched their origins and etymology of some antropotoponims.